Targeted Co-delivery of Tumor Antigen and α-Galactosylceramide to CD141+ Dendritic Cells Induces a Potent Tumor Antigen-Specific Human CD8+ T Cell Response in Human Immune System Mice - Huang, Jing; Zhou, Jing; Ghinnagow, Reem; Seki, Toshiyuki; Iketani, Sho; Soulard, Daphnée; Paczkowski, Patrick; Tsuji, Yukiko; MacKay, Sean; Cruz, Luis Javier; Trottein, François; Tsuji, Moriya (Frontiers in Immunology, 2020)
Active co-delivery of tumor antigens (Ag) and α-galactosylceramide (α-GalCer), a potent agonist for invariant Natural Killer T (iNKT) cells, to cross-priming CD8α+ dendritic cells (DCs) was previously shown to promote strong anti-tumor responses in mice. Here, we designed a nanoparticle-based vaccine able to target human CD141+ (BDCA3+) DCs - the equivalent of murine CD8α+ DCs - and deliver both tumor Ag (Melan A) and α-GalCer. This nanovaccine was inoculated into humanized mice that mimic the human immune system (HIS) and possess functional iNKT cells and CD8+ T cells, called HIS-CD8/NKT mice. We found that multiple immunizations of HIS-CD8/NKT mice with the nanovaccine resulted in the activation and/or expansion of human CD141+ DCs and iNKT cells and ultimately elicited a potent Melan-A-specific CD8+ T cell response, as determined by tetramer staining and ELISpot assay. Single-cell proteomics further detailed the highly polyfunctional CD8+ T cells induced by the nanovaccine and revealed their predictive potential for vaccine potency. This finding demonstrates for the first time the unique ability of human iNKT cells to license cross-priming DCs in vivo and adds a new dimension to the current strategy of cancer vaccine development.